Comparison of the quality of life of young university athletes and young soldiers from the Brazilian Pantanal (Agora for Physical Education and Sport, 2021)
The research compares the quality of life between military and university students. Cross-sectional study with a descriptive design, with 206 physically active male participants, 101 university students deported and 105 young soldiers with a mean age of 19.4 years. The necessary care for the IPAQ, cropped version to select participants with the level of “active” physical activity and Whoqol-bref to identify the level of quality of life. Response data were grouped into 4 different domains: Physical, Psychological, Social Relations and Environment; The results showed a better perception of quality of life and risk factors such as nutritional status and tobacco use among young soldiers in relation to university students.
Keywords: Whoqol-bref; university students; young soldiers